Phytoplankton Abundance and Diversity in the Coastal Waters of Lalang Village, Siak Regency - Ritonga, Agnesia; Zulkifli, Zulkifli; Siregar, Yusni Ikhwan (Journal of Coastal and Ocean Sciences, 2023)
This research was conducted in May 2022 in the coastal waters of Lalang Village, Siak Regency. This study aims to analyze the abundance and diversity of phytoplankton. The method used is the survey method by determining the sampling location by purposive sampling. Based on the results of the study, 6 species of phytoplankton were found in the coastal waters of Lalang Village, Siak Regency, namely Nitzschia sp, Isthmia sp, Navicula, Dactylococcopsis sp, Flagilaria sp, and Synedra sp. The average value of abundant phytoplankton at station 1 ranged from 1,938.61 to 479.68; at station 2 it ranged from 3,046.40 to 479.68; at station 3 it ranged around 1,384.72 to 479.68. Based on the results, the abundance of phytoplankton at each station was significant